American Gothic: Reflections on Gothic Architectural Scholarship in America, 1925-2025 - Bork, Robert (AVISTA Studies in the History of Medieval Technology, Science, and Art, 2025)
This book chronicles the contributions of American scholars to the study of European Gothic architecture. It traces this history through a series of biographical case studies of major figures ranging from Arthur Kingsley Porter to Robert Branner and Jean Bony to Caroline Bruzelius, calling attention to their influence as mentors and to the character of their professional networks. These biographical chapters are supplemented by thematic essays and a roundtable discussion of current issues in the field. Altogether, the book explains how working from overseas presents both significant challenges and valuable perspectives, allowing American scholars to enrich dialog in the field. Contributors are: Robert Bork, Caroline Bruzelius, Meredith Cohen, S. Diane Daussy, Jennifer M. Feltman, Erin Hulbert, Maile Hutterer, Matthew Reeve, Lisa Reilly, Rebecca Smith, Zachary Stewart, Kyle Sweeney, Kristine Tanton, Sarah Thompson, Arnaud Timbert, and Joseph Williams.